The family meetings in oncology: some practical guidelines - Gritti, Paolo (Frontiers in Psychology, 2015)
Somatic illness is not only an individual experience of physical and psychological suffering, but also a psychosocial status that modulates the patient’s interpersonal relationships. Receiving a diagnosis of cancer causes severe distress. The patient’s family, too, feels the emotional ups and downs of the patient. Like the patient, they feel distressed during the onset, course and outcome of the disease. Minimizing the interpersonal impact of the illness contributes to an improved quality of life for both patients and caregivers. Thus, it is widely assumed that cancer treatments should include some kind of psychological support for the patient and family members. All of these treatments are aimed at improving collaboration and illness perception among family, patients and healthcare professionals, and support the family during the course of the disease and cancer therapies. The family system theory is a valuable framework to explain how the disease of the patient and the family's daily life are interconnected. The therapeutic alliance with the family is a powerful tool to improve the quality of life for the patient, as well as to relieve the psychological distress of the family members who are involved. The following pages describe the objectives and conversational techniques that can be a tool for psychosocial work with the family of a cancer patient. The goal of this intervention is to help the patient’s family to understand their problems and acknowledge the anxiety and fear of mourning that can impede their capacity to face the everyday problems they must cope with. To achieve this goal, it is recommended that a meeting (or a series of meetings) be scheduled, and conducted both in hospital and in the home. The steps to set up and conduct a family meeting are described in the paper, with special emphasis on communication skills required to meet family expectations and discuss the crucial issues of their everyday life.